Early surgical intervention in pediatric trauma patients with GCS 3 – Results of 8 Years experience - Merve Boyraz; Servet Yüce; Abdulrahman Özel; Mehmet Tolgahan Örmeci; Hasan Özen; Süleyman Akkaya; Edin Botan (World Neurosurgery: X)
Objectives: Traumatic brain injury (TBI) is the leading cause of death and disability in children. Mortality and morbidity increase dramatically in patients with severe brain injury and a Glasgow Coma Scale (GCS) score of 3. This study evaluates the impact of early surgery (within 0–6 h) on mortality and morbidity in this patient group, often considered ''hopeless cases.'' Methods: Children with TBI and a GCS score of 3 admitted to the Pediatric Intensive Care Unit of Van Training and Research Hospital between 2016 and 2024 were retrospectively analyzed. Medical records, imaging studies, and outcomes were reviewed. Mortality and neurological sequelae were assessed within one year using the Glasgow Outcome Scale (GOS). Results: Among 514 children admitted with isolated head trauma, 11.3 % (n = 58) had a GCS score of 3. Twelve patients (20.7 %) died within the first 4 h due to hemodynamic instability and were excluded. Of the remaining 46 patients, 14 (30.4 %) underwent cranial surgery, while 32 (69.6 %) received medical treatment. Mortality rates were 50 % (7/14) in the surgical group and 71.8 % (23/32) in the medical group (p = 0.137). Neurological sequelae were significantly lower in the surgical group (14.3 % vs. 77.8 %, p = 0.020). Early surgery (within 6 h) resulted in lower mortality (25 % vs. 83.3 %, p = 0.005) and better neurological outcomes, with all survivors discharged neurologically intact. In contrast, the only survivor operated on after 6 h had neurological sequelae. Conclusion: Early decompressive craniectomy (within 6 h) significantly reduces mortality and neurological sequelae in pediatric patients with severe TBI (GCS: 3). These patients should not be dismissed as ''hopeless'' but given the opportunity for surgical intervention.